Current perspectives in coronary microvascular dysfunction. (January 2017) - Shome, Joy S.; Perera, Divaka; Plein, Sven; Chiribiri, Amedeo
Abstract: The coronary arterial system consists of large epicardial coronary arteries, pre‐arterioles, and arterioles, which together closely regulate CBF. Structural, functional, and extravascular abnormalities of the microcirculation lead to CMD. CMD can present with symptoms suggestive of CAD, often in the absence of significant obstructive epicardial CAD. Conventional invasive angiography does not allow direct visualization of the microcirculation. Invasive indices, such as CBF and CFR, and non‐invasive imaging modalities, such as CMR and PET, can be used to quantify absolute MBF and enable a direct and accurate assessment of coronary microvascular function. CMD appears to be more prevalent in women, typically presenting with symptoms of ischemia with unobstructed coronary arteries, and has a relatively unfavorable prognosis. CMD is classified clinically depending on the presence or absence of epicardial CAD, myocardial disease, or iatrogenic causes. Although invasive intracoronary techniques can be used to detect CMD, these cannot provide insight into the mechanisms involved in its pathogenesis. Imaging modalities such as CMR and cardiac PET are becoming indispensable tools in the evaluation of suspected CMD.